Penta-Coordinated Transition Metal Macrocycles as Electrocatalysts for the Oxygen Reduction Reaction - Zagal-Moya, J; Zagal-Moya, J; Tasca-Gottardo, F; Tasca-Gottardo, F (Springer Science and Business Media Deutschland GmbH, 2021)
The oxygen reduction reaction (ORR) is a highly important reaction in electrochemistry. The following short review details recent advances in novel non-precious metal catalysts containing transition metal macrocycles for use in the ORR. Unbound, many of these electrodes were found to generate high levels of side products such as O2− and H2O2 via 2-electron processes, and for this reason, it is aimed to create systems which would favor a 4-electron process which would completely convert oxygen to H2O. The 4-electron reduction of O2 releases the most energy in a fuel cell. Novel catalytic materials containing metal macrocycles were created mimicking the structure of enzyme metal centers, the metal in the macrocycle bound to a fifth axial ligand. These structures were observed to exhibit improved catalytic activity, and in the case of cobalt, phthalocyanine systems were observed to move away from the inefficient 2-electron process towards the more complete 4-electron process in alkaline media. Both experimental results (XPS, EPR, cyclic voltammetry and polarization curves) and theoretical models were gathered for various pentacoordinate systems and various electronic effects of the axial ligand on metal center were proposed. Penta-coordinate macrocycles are an important tool for further manipulating and tuning the electronic behavior of transition metal centers for catalysis of the ORR. © 2020, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Oxygen reduction reaction; Metal macrocycles; Axial ligands; O-2 bond-cleavage; 4-electron reaction